Impacts of Covid-19 and Lockdown on Mental Health: Depression, Anxiety, Stress and Fear among Adult Population in Turkey - Bener, Abdulbari; Griffiths, Mark D; Bar?sik, Cem Cahit; Inan, Funda Catan; Morg, Ebru (Archives of Clinical and Biomedical Research, 2022)
Background: Most of the documented literature to date has reported that the COVID-19 pandemic is associated with greater distress, anxiety, anger, stress, and agitation among the general public compared to before the onset of the pandemic. Method and study design: A review was done to now the evidence for the antiviral and immune-modulatory properties of micronutrients. A search was done in PubMed, Scopus, and Google Scholar for the nutrients with proven effect against viral infection. Experimental studies, clinical studies, reviews, and meta-analyses were studied descriptively. Aim: The aim of study was to examine the impact of COVID-19 and the national lockdown on mental health perception of depression, anxiety, stress and fear among the general population in Turkey. Subjects and methods: The present study comprised a cross-sectional survey of 1,792 male and female participants aged 20-65 years in Turkey (June to October 2020) who completed the 21-item Depression, Anxiety, Stress Scale (DASS-21) and Fear of COVID-19 Scale (FCV-19S). Bivariate and multivariate stepwise regression analyses were used for the demographic and mental health-related variables. Results: The majority of the respondents recognized the main COVID-19 symptoms (82.9%), knew that there is no drug and vaccine (85.4%), were afraid to travel and visit a shopping mall (86.9%), believed wearing medical masks helped prevent against COVID-19 (81.1%), and considered lockdown isolation reduced the risk of COVID-19 (86.5%). The mean score (and standard deviation) for depression was 13.57 (SD±8.48); for anxiety was 9.32 (SD±7.62); for stress was 16.45 (SD±6.89); and for fear of COVID-19 was 23.47 (SD±4.24). The study sh